Depression and Anxiety in the Postnatal Period: An Examination of Infants' Home Language Environment, Vocalizations, and Expressive Language Abilities. Issue 6 (3rd August 2020) - Brookman, Ruth; Kalashnikova, Marina; Conti, Janet; Xu Rattanasone, Nan; Grant, Kerry‐Ann; Demuth, Katherine; Burnham, Denis
Abstract : This longitudinal study investigated the effects of maternal emotional health concerns, on infants' home language environment, vocalization quantity, and expressive language skills. Mothers and their infants (at 6 and 12 months; 21 mothers with depression and or anxiety and 21 controls) provided day‐long home‐language recordings. Compared with controls, risk group recordings contained fewer mother–infant conversational turns and infant vocalizations, but daily number of adult word counts showed no group difference. Furthermore, conversational turns and infant vocalizations were stronger predictors of infants' 18‐month vocabulary size than depression and anxiety measures. However, anxiety levels moderated the effect of conversational turns on vocabulary size. These results suggest that variability in mothers' emotional health influences infants' language environment and later language ability.